The Measurement Performance of the Parkinson's Disease Activities of Daily Living, Interference, and Dependence Instrument - Deal, Linda S.; Andrae, David A.; Myers, Daniela E.; Johnson, Nathan; Foster, Brandon; Evans, Christopher J. (Frontiers in Neurology, 2022)
Parkinson's disease is a neurodegenerative disease that can be associated with motor fluctuations that result in substantial negative impact to an individual's activities of daily living. Understanding the patient's perspective about the impact of Parkinson's disease therapies is an important part of drug development and shared treatment decision-making. The objective of this research was to examine the structure, scoring, internal consistency, test-retest reliability, and concurrent and known groups validity of the Parkinson's Disease Activities of Daily Living, Interference and Dependence (PD-AID) instrument, a new, patient-reported outcomes instrument, developed to assess the clinical benefit of Parkinson's disease treatment from the patient's perspective. This was a non-interventional study among persons with mild-to-moderate Parkinson's disease currently using and responding to L-Dopa. The structure of the measure was confirmed applying item response theory to data from baseline, supporting 4 candidate scores. Baseline Patient Global Impression of Severity ratings facilitated known-groups analysis. Data from all participants were used to estimate test-retest reliability. Concurrent validity was assessed using correlations with related measures. Participants (n = 94) were mean age 69 years (mean time since diagnosis 6.9 years); 34 experienced L-Dopa-related dyskinesia. Psychometric models supported 4 candidate scoring regimes for the PD-AID. All exhibited adequate reliability and validity characteristics and strong internal consistency. Correlations with reference measures were in the expected direction and range of magnitude. Analyses supported the PD-AID as fit-for-purpose, producing psychometrically sound scores. Further research to confirm the measurement properties of the PD-AID in an expanded sample and to establish thresholds for meaningful score changes is recommended.